2017
DOI: 10.1155/2017/9302328
|View full text |Cite
|
Sign up to set email alerts
|

Helping Elderly Users Report Pain Levels: A Study of User Experience with Mobile and Wearable Interfaces

Abstract: Pain is usually measured through patient reports during doctor visits, but it requires regular evaluation under real-life conditions to be resolved effectively. Over half of older adults suffer from pain. Chronic conditions such as this one may be monitored through technology; however, elderly users require technology to be specifically designed for them, because many have cognitive and physical limitations and lack digital skills. The purpose of this article is to study whether mobile or wearable devices are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Previous studies on remote monitoring devices for older users have placed sensors on the trunk, sacrum, abdomen, chest, wrist, pocket or neck, with some placing sensors on several locations (e.g., chest, wrist, thigh and ankle) [ 6 ]. Although, e.g., the wrist has been found to be preferred by young users [ 69 ], older users have not declared a clear preference [ 33 ], and in our observations, in people using support devices, the wrist often remains stationary. Our device was placed on the back of the users, with users finding it to be comfortable and feeling it provided some type of support.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Previous studies on remote monitoring devices for older users have placed sensors on the trunk, sacrum, abdomen, chest, wrist, pocket or neck, with some placing sensors on several locations (e.g., chest, wrist, thigh and ankle) [ 6 ]. Although, e.g., the wrist has been found to be preferred by young users [ 69 ], older users have not declared a clear preference [ 33 ], and in our observations, in people using support devices, the wrist often remains stationary. Our device was placed on the back of the users, with users finding it to be comfortable and feeling it provided some type of support.…”
Section: Discussionmentioning
confidence: 51%
“…A recent study found the wrist to be the preferred placement of a wearable, followed by the chest, and finally, the waist [ 32 ]. Another study found that older users showed no clear preference over placement of a wearable on the arm, neck, waist or wrist [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, their preference for data input methods could be different. It is reported that the elderly prefer wearable devices over mobile applications, [53,54] i.e., the active mode of data input in a simplified way [54]. Nevertheless, the wearable device could only be helpful to input pain intensity, whereas there are some other attributes of pain data to be input as well.…”
Section: Rq32: What Are the Pain Data Input Modes Involved?mentioning
confidence: 99%
“…Healthcare providers are increasingly tracking users in their daily routines at home; this can provide rich information to support accurate and cheaper treatment [8] or help to self-report pain and emotions [5,13]. In pre-digital times, data to support healthcare was logged through analogue methods, such as keeping a diary or a logbook, putting coins in a jar or cutting a spike from a comb.…”
Section: Introductionmentioning
confidence: 99%
“…Larsen et al [8] present how the instrumentation of a wearable one-button tracker can result to deeper investigative dialogue about personal sensations based on the data. Rodríguez et al [13] suggest selfmonitoring through wearable interfaces to collect realtime information from chronic-pain patients. On the same note, researchers have been studying subjective self-reporting of emotions through digital interfaces, and found a potential for tangible user interfaces [5].…”
Section: Introductionmentioning
confidence: 99%